Diet Effect, Life Table, Physiological Tolerances, Dispersal Activity And Toxicological Studies Of The Rove Beetle, Paederus Fuscipes Curtis (Coleoptera: Staphylinidae) - Bong, Lee Jin (2013)
Biological and ecological aspects of Paederus fuscipes Curtis namely: (1) effects of diet on the fitness and reproduction development; (2) population growth capacity; (3) desiccation and temperature tolerance; and (4) impact of climatic factors and mechanical disturbances on the adult dispersal, were focused in this study to provide insight into how the above mentioned factors influence the insect infestation into human dominated areas, and (5) toxicological studies were carried out to aid the authorities in planning for a better control programme. The longevity of 42 to 43 days and substantial numbers of egg laid (121 eggs per female) were recorded in protein-rich diet fed adults. This showed that protein source is a necessity to P. fuscipes for optimal fitness and reproduction. This study also showed that carbohydrate-rich diet fed adults had extended life span (64 to 74 days) but the reproductive rate decreased. An adequate intake of lipid diet was reported beneficial to reproduction, but too much in the diet was detrimental to both survival and reproduction in adult P. fuscipes.